Pengembangan Daya Tarik Wisata Pantai Pandawa: Peran Strategis Pemangku Kepentingan - Kirana , Ni Putu Intan (Journal of Tourism and Hospitality Analysis (JoTHA), 2025)
Pandawa Beach is one of the leading tourist attractions in Badung Regency, Bali, which has developed rapidly from a formerly hidden secret beach into a community-based tourism destination. Its development cannot be separated from the contribution and collaboration of multiple tourism stakeholders. This study aims to identify the stakeholders involved in the development of Pandawa Beach tourist attraction and to analyze their respective roles in the development process. A qualitative approach was employed using observation, in-depth interviews, and documentation as data collection techniques. The analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing. The findings show that stakeholder involvement is divided into three categories, namely key stakeholders, primary stakeholders, and secondary stakeholders. The roles of the stakeholders also vary according to their functions, classified as policy creators, coordinators, facilitators, implementers, and accelerators. The study concludes that the synergy of diverse stakeholders has contributed to the development of Pandawa Beach; however, collaboration is not yet optimal, particularly in long-term marketing strategies. Strengthening stakeholder partnerships and integrated promotional efforts is needed to support sustainable tourism development in Pandawa Beach.